Severe early-onset anemia disproportionate to hyperbilirubinemia in a Rh isoimmunized neonate - Jassal, Monica; Kaur, Ravneet; Chawla, Deepak; Jain, Suksham (Indian Journal of Child Health, 2020)
Rhesus isoimmunized neonates presenting with hyperbilirubinemia needing exchange transfusion and late-onset anemia is commonly known; however, severe early-onset anemia without significant neonatal jaundice, requiring packed red cell transfusion, is less commonly reported. Index case presented with serial fall in hematocrit levels needing PRBC transfusions and intravenous immunoglobulin infusion to prevent recurrent need for blood transfusion.